Silent but brewing: reactive ethnicity and interculturality among Chinese students in Singapore - Chib, Arul (2018)
The study takes an indirect approach towards the intercultural experience of migrants and explores how they perceive discrimination from host society and in turn stereotype it. Previous studies have highlighted how interculturality facilitates the adaptation of migrants in the host country. This study explores (i) how face-to-face (FTF) and mediated contact and perceived discrimination predict stereotyping, and (ii) how contact, perceived discrimination and stereotyping predict interculturality. A web-based survey was conducted among university students from the People’s Republic of China (n = 585) in Singapore. FTF contact reduced stereotyping better than mediated contact. Perceived discrimination increased stereotyping of the host society by migrants, whereas stereotyping negatively affected interculturality. The study calls for better contact between locals and the migrant population.